Two cytosolic components of the human neutrophil respiratory burst oxidase translocate to the plasma membrane during cell activation. - Clark, R A (1990)
The superoxide-forming respiratory burst oxidase of human neutrophils is composed of membrane-associated catalytic components and cytosolic constituents required for oxidase activation. This study concerns the hypothesis that cytosolic oxidase components translocate to a membrane fraction when neutrophils are stimulated and the oxidase is activated. A polyclonal antiserum that recognizes two discrete cytosolic oxidase components of 47 and 67 kD was used to probe transfer blots of electrophoresed membrane and cytosol fractions of resting and stimulated neutrophils. In contrast to their strictly cytosolic localization in unstimulated cells, both proteins were detected in membrane fractions of neutrophils activated by phorbol esters and other stimuli. This translocation event was a function of stimulus concentration as well as time and temperature of exposure to the stimulus. It was inhibited by concentrations of N-ethylmaleimide that blocked superoxide formation but was unaffected by 2-deoxyglucose. There was a correlation between translocation of the cytosolic proteins and activation of the oxidase as determined by superoxide formation. Quantitative analyses suggested that approximately 10% of total cellular p47 and p67 became membrane-associated during phorbol ester activation of the oxidase. Analysis of Percoll density gradient fractions indicated that the target membrane for translocation of both proteins was the plasma membrane rather than membranes of either specific or azurophilic granules. In the cell-free oxidase system arachidonate-dependent but membrane-independent precipitation of the cytosolic oxidase proteins was demonstrated. The data show that activation of the respiratory burst oxidase in stimulated human neutrophils is closely associated with translocation of the 47- and 67-kD cytosolic oxidase components to the plasma membrane. We suggest that this translocation event is important in oxidase activation.